2004
DOI: 10.1016/s0266-7681(03)00220-1
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Conservative Management of Mallet Finger

Abstract: This prospective study assessed the results of a custom-made thermoplastic splint for treatment of mallet finger deformity. From April 1999 to April 2000, 42 patients with mallet finger deformity were recruited. All patients were seen within 1 week and treated with a thermoplastic splint custom-made by the hand therapy department. The splint was simple to make, easy to fit and suitable for all finger shapes and sizes. It improved the deformity in 30 out of 34 cases, and caused no skin irritation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…This development should be in line with the priorities of HSE who state that 'the focus will be on standardizing care and implementing proven solutions to save lives, prevent complications, remove waiting lists and save money' ( p. 3). 1 Many authors to date 13,14,[16][17][18] have provided evidence of service delivery initiatives, which have indeed achieved these improvements sought by the HSE, and provide a template that is transferrable to the Irish health-care system. The widespread establishment of a model of service delivery, which facilitates direct referral from the emergency department to the occupational therapist would reduce delays and disruption in treatment access and provide the patient with the appropriate care at the appropriate time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This development should be in line with the priorities of HSE who state that 'the focus will be on standardizing care and implementing proven solutions to save lives, prevent complications, remove waiting lists and save money' ( p. 3). 1 Many authors to date 13,14,[16][17][18] have provided evidence of service delivery initiatives, which have indeed achieved these improvements sought by the HSE, and provide a template that is transferrable to the Irish health-care system. The widespread establishment of a model of service delivery, which facilitates direct referral from the emergency department to the occupational therapist would reduce delays and disruption in treatment access and provide the patient with the appropriate care at the appropriate time.…”
Section: Resultsmentioning
confidence: 99%
“…The literature indicates that mallet injury can be managed in the emergency department, 9 general practice, 10,11 consultant-led clinics 12 and therapy-led clinics. [13][14][15] In an Irish context, emergency departments are most likely to provide the first point of contact for many of these patients. While appropriate diagnosis and treatment in the emergency department is critical to the ultimate outcome, 'closed tendon injuries of the hand are unfortunately often not treated with the same respect as other hand injuries' (p. 76), 9 thereby adding to the risk of long-term disability or deformity.…”
Section: Mallet Finger and Managementmentioning
confidence: 99%
“…Richards and colleagues published a series of 34 patients treated with a custom thermoplastic splint and reported 30 of 34 successful outcomes based on Abouna and Brown's criteria. 2 Few comparative studies are available regarding splinting techniques for mallet deformity. Warren et al compared the Abouna splint with the Stack splint across 116 patients and found no difference in final improvement in extensor lag.…”
Section: Discussionmentioning
confidence: 99%
“…For non-complicated cases some authors recommend conservative treatment, usually by splinting or casting [1][2][3][4][5]. Under some conditions, however, operation is much more preferred, as suggested by various published reports [6][7][8].…”
Section: Introductionmentioning
confidence: 99%